Dominant Factors in Complementary Food Feeding in Babies and Toddlers - Amrina Octaviana; Roslina Roslina; Indah Trianingsih; Marlina Marlina; Nelly Indrasari (Jurnal Kesehatan)
During the first two years of their lives, 52.8% of Indonesian children aged 6–23 months did not receive the nutrition they needed to grow and develop optimally. In 2019, Tulang Bawang Regency was one of the areas in Lampung province with the most significant percentage of very underweight toddlers (BB/TB) at 7.7%. Of the nine health centers, the lowest infant health service coverage was at the Banjar Baru Health Centre, Tulang Bawang Regency. The research aims to determine the dominant factors in giving MP-ASI to babies and toddlers in Tulang Bawang Regency in 2021. This research is correlational-analytic with a cross-sectional approach. Sampling used a stratified random sample of 132 mothers with babies and toddlers aged 6–24 months. Bivariate analysis uses the chi-square test, and multivariate analysis uses the logistic regression test. The results show that internal factors (age familiarity with food, child activity, and child health history) and some external factors (type of food, frequency of feeding, number of feedings, and community culture) have a significant relationship with MP-ASI feeding behavior in babies and toddlers (p